2012
DOI: 10.1111/j.1471-0528.2012.03301.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of urinary incontinence 20 years after childbirth: a national cohort study in singleton primiparae after vaginal or caesarean delivery

Abstract: Objective To investigate the prevalence and risk factors for urinary incontinence (UI) 20 years after one vaginal delivery or one caesarean section.Design Registry-based national cohort study.Setting Women who returned postal questionnaires (response rate 65.2%) in 2008.Population Singleton primiparae who delivered in the period [1985][1986][1987][1988] with no further births (n = 5236).Methods The Swedish Pregnancy, Obesity and Pelvic Floor (SWEPOP) study linked Medical Birth Register (MBR) data to a question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
117
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(145 citation statements)
references
References 32 publications
11
117
1
9
Order By: Relevance
“…Gyhagen et al compared the prevalence of UI between women who delivered vaginally and by cesarean section. 20 UI was 67% higher after a vaginal delivery (40.3%) compared to women who had undergone caesarean section (28.8%), (OR 1.67; 95% CI 1.45-1.92). Follow up of women 10 years after delivery, showed that prevalence was 10.1% after vaginal delivery compared with 3.9% after caesarean section (odds ratio [OR] 2.75; 95% CI 2.02-3.75).…”
Section: Discussionmentioning
confidence: 97%
“…Gyhagen et al compared the prevalence of UI between women who delivered vaginally and by cesarean section. 20 UI was 67% higher after a vaginal delivery (40.3%) compared to women who had undergone caesarean section (28.8%), (OR 1.67; 95% CI 1.45-1.92). Follow up of women 10 years after delivery, showed that prevalence was 10.1% after vaginal delivery compared with 3.9% after caesarean section (odds ratio [OR] 2.75; 95% CI 2.02-3.75).…”
Section: Discussionmentioning
confidence: 97%
“…Movahedi et al, found a 1% higher occurrence of UI in caesarean section versus vaginal delivery [22]. Another study concluded the protective effects of CS upon incontinence are complex, yet there seems to be a strong effect on the prevention of pelvic organ prolapse and elective caesarean section [23].…”
Section: Discussionmentioning
confidence: 99%
“…According to Pregazzi et al 66 , detailed classifi cation of perineal ruptures immediately after delivery is not proven to be a good predictor of the occurrence of pelvic relaxation and stress urinary incontinence. Th e risk of developing urinary incontinence was found to be by 67%-71% higher after vaginal delivery as compared to cesarean section in a population-based cohort of singleton primiparae 67 . Fritel et al state that routine mediolateral episiotomy in a population of primiparae does not protect against the appearance of urinary incontinence in 4-year period after vaginal delivery, while the risk of anal incontinence is increased 68 .…”
Section: Impact Of Episiotomy On Urinary Incontinence After Deliverymentioning
confidence: 99%